Gone with the fire: Market reaction to cryptocurrency exchange shutdown - Hanol Lee; Dainn Wie (ZBW - Leibniz Information Centre for Economics, 2022)
Disruption of exchanges frequently happens in the cryptocurrency market, though their potential impacts are relatively under-investigated. This study employs a 20-hour service interruption on October 15th, 2022, at Upbit, the dominant cryptocurrency exchange in Korea, as an exogenous shock of service interruption on the cryptocurrency market. Event study estimation shows that the change in abnormal returns depends on how important the specific exchange is to those cryptocurrencies. Cryptocurrencies predominantly traded on Upbit showed sharp reactions to both service disruption and recovery, while major currencies such as Bitcoin and Ethereum presented limited reactions to service interruption only.
Keywords: G12; G14; G15; G23; 330; Cryptocurrency; abnormal return; Event study; Network service disruption